Variables sociodemográficas en consultantes que abandonan el proceso terapéutico - Erazo Pérez, Diego Fernando (2020)
Dropout has been considered a problem that has affected psychologists in private and public practices. This study tries to answer the question: are there any differences between those who leave the therapeutic process with those who do not? The general objective of this study is to identify sociodemographic variables that are related to therapeutic abandonment in adult population that attend to a process in a center of psychological care, then describe the variables and contrast them among clients who leave the therapeutic process with those who do not. The focus of this research is quantitative, with a non-experimental and cross-sectional design. Scope is comparative and correlational between the sociodemographic variables of level of education, age and gender between clients who abandoned the therapeutic process with those who did not abandoned it. This study analyzed the information from an existing database belonging to a university psychological care center in the city of Quito. The results indicated that 51.3 per cent of the clients did not complete the psychotherapeutic process. The mean age of the clients who abandoned the process was 32 year, no significant gender differences were found between those that abandoned and those who do not abandoned the process, clients who has achieved high school level of education were those that abandoned the most. The logistic regression indicated that none of the variables significantly predicted the abandonment of the process. Therapeutic abandonment it is considered a problem because of the high percentage of dropouts that reflect this and other investigations. That is why there should be more studies that show analysis of other variables like therapeutic alliance and adherence.